Thrilling Encounters in Social Settings: A Retelling of The Eyes of Darkness by Dean Koontz - Ali, Muhammad Ilham; Jannah, Sabrina Wardhatul; Pabur, Herminus Efrando; Katili, Yayu Anggraini H (Fakultas Sastra - Universitas Muslim Indonesia, 2024)
This study analyzes the social situations depicted in the novel